2012
DOI: 10.1179/1751584x12y.0000000021
|View full text |Cite
|
Sign up to set email alerts
|

Micropolar fluid squeeze film lubrication between rough anisotropic poroelastic rectangular plates: special reference to synovial joint lubrication

Abstract: The effect of anisotropic permeability on micropolar squeeze film lubrication between poroelastic rectangular plates is studied. The non-Newtonian synovial fluid is modelled by Eringen's micropolar fluid, and the poroelastic nature of cartilage is taken in to account. The stochastic modified Reynolds equation, which incorporates the elastic as well as randomised surface roughness structure of cartilage with micropolar fluid as lubricant, is derived. Modified equations for the mean fluid film pressure, mean loa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Their research indicated that the impacts of pair stresses increase both steady-state and dynamic stiffness and damping properties. Savitramma and Naduvinamani [30] studied the effects of surface roughness and poroelasticity on the micropolar squeeze film behavior between rectangular plates and discovered that the influence of surface roughness has significant implications on the synovial joint lubrication mechanism. Al Atawi et al [31] presented a synovial joint study recently and investigated the effect of different parameters such as the porosity and viscoelasticity of articular cartilages on the flow of steady convective diffusion in synovial joint by utilizing the finite volume method combined with the Beavers and Joseph conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Their research indicated that the impacts of pair stresses increase both steady-state and dynamic stiffness and damping properties. Savitramma and Naduvinamani [30] studied the effects of surface roughness and poroelasticity on the micropolar squeeze film behavior between rectangular plates and discovered that the influence of surface roughness has significant implications on the synovial joint lubrication mechanism. Al Atawi et al [31] presented a synovial joint study recently and investigated the effect of different parameters such as the porosity and viscoelasticity of articular cartilages on the flow of steady convective diffusion in synovial joint by utilizing the finite volume method combined with the Beavers and Joseph conditions.…”
Section: Introductionmentioning
confidence: 99%